144k views
5 votes
2x-7y= -1
3x- 5y = -4

User Thirumal
by
5.7k points

1 Answer

5 votes

Answer:

y=-5/11 and x=-23/11

Explanation:

We can use the elimination method

We have

2x-7y= -1 and

3x- 5y = -4

We can multiply the first equation by 3 and the second by 2. This gives us

3(2x-7y)= -1(3) and

2(3x- 5y) = -4(2)

Distributing and simplifying results in

6x-21y=-3 and

6x-10y=-8

Subtracting the second equation from the first, we get

0x-11y=5

-11y=5

y=-5/11

putting this into the first equation, we get

2x-7(-5/11)=-1

2x+35/11=-1

x=(-1-35/11)/2

x=-23/11

User Sisis
by
5.2k points